h=-2(t-1)-16t(t-1)

Simple and best practice solution for h=-2(t-1)-16t(t-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h=-2(t-1)-16t(t-1) equation:


Simplifying
h = -2(t + -1) + -16t(t + -1)

Reorder the terms:
h = -2(-1 + t) + -16t(t + -1)
h = (-1 * -2 + t * -2) + -16t(t + -1)
h = (2 + -2t) + -16t(t + -1)

Reorder the terms:
h = 2 + -2t + -16t(-1 + t)
h = 2 + -2t + (-1 * -16t + t * -16t)
h = 2 + -2t + (16t + -16t2)

Combine like terms: -2t + 16t = 14t
h = 2 + 14t + -16t2

Solving
h = 2 + 14t + -16t2

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Simplifying
h = 2 + 14t + -16t2

See similar equations:

| XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 | | 4(3x+8)=32 | | 9x+4=5x+2 | | -3(x-4)+5=-2z-2 | | 5x^4=20x^6 | | 10d+6-6d=22 | | -3(x+8)=-15 | | -5(2.5+x)=10 | | -9x^2+120x-12=0 | | -1(-3x-5)=-7 | | 0.7+y=-1.63 | | 125m-100m+43650=45225-200m | | 6/5=2/5x | | 3=-3(4x+6) | | y=(x^3-6x^2-x+6)(x^2-2x+5) | | 6/-16 | | 3x-12=4x+2-x | | 2x-4=-x-5 | | e^5x=26 | | 5[x-6]+2=7x-6 | | 7c+2=31 | | -2x-12=-6(2+6n) | | y=(x-6)(x^2-1) | | 3(2x-5)-6(2x-6)= |

Equations solver categories